Base/Cryptand/Metal‐Free Automated Nucleophilic Radiofluorination of [18F]FDOPA from Iodonium Salts: Importance of Hydrogen Carbonate Counterion. Issue 48 (16th December 2018) - Maisonial‐Besset, Aurélie; Serre, Audrey; Ouadi, Ali; Schmitt, Sébastien; Canitrot, Damien; Léal, Fernand; Miot‐Noirault, Elisabeth; Brasse, David; Marchand, Patrice; Chezal, Jean‐Michel
Abstract : As evidenced by the number of publications and patents published in the last years, the radiosynthesis of 6‐[ 18 F]fluoro‐3, 4‐dihydroxy‐ L ‐phenylalanine ([ 18 F]FDOPA) using the nucleophilic [ 18 F]F‐ process remains currently a challenge for the radiochemists scientific community even if promising methods for the radiofluorination of electron‐rich aromatic structures were recently developed from arylboronate, arylstannane or iodonium salt precursors. In such context, based on the use of an iodonium triflate salt precursor, we optimized a fast and efficient radiofluorination route fully automated and free from any base, cryptand or metal catalyst for the radiosynthesis of [ 18 F]FDOPA. Using this method, this clinically relevant radiotracer was produced in 64 min, 27–38 % RCY d.c. (n = 5), >99 % RCP, >99 % ee., and high Am 170–230 GBq/µmol. In addition, this optimization study clearly highlighted the important role of a triflate‐hydrogen carbonate counterion exchange during the radiolabeling process to achieve high fluorine‐18 incorporation yields. Abstract : [ 18 F]FDOPA challenge: A new radiosynthetic route to [ 18 F]FDOPA was developed and fully automated from a key iodonium triflate salt precursor. This radiotracer was produced via a "minimalist approach" (see figure) involving nucleophilic [ 18 F]F – process, without any use of base, cryptand or metal catalyst, in 64 min, 27–38 % RCY, >99 % RCP, > 99 % ee., and high Am 170–230 GBq.µmol –1 (n = 5).